2020
DOI: 10.1016/j.ipej.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac electrophysiology consultative experience at the epicenter of the COVID-19 pandemic in the United States

Abstract: Background The COVID-19 pandemic has greatly altered the practice of cardiac electrophysiology around the world for the foreseeable future. Professional organizations have provided guidance for practitioners, but real-world examples of the consults and responsibilities cardiac electrophysiologists face during a surge of COVID-19 patients is lacking. Methods In this observational case series we report on 29 consecutive inpatient electrophysiology consultations at a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…Arrhythmias were also prevalent among 44% of patients in early reports following the emerged COVID-19 outbreak in Wuhan, China [ 33 ]. Atrial arrhythmias are the most commonly reported types, with atrial fibrillation consultations commonly requested during the peak of the COVID-19 outbreak in New York [ 34 ]. Other less common arrhythmias included ventricular arrhythmias, ventricular tachycardia storm, atrioventricular block, inappropriate sinus tachycardia, and postural orthostatic tachycardia syndrome [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias were also prevalent among 44% of patients in early reports following the emerged COVID-19 outbreak in Wuhan, China [ 33 ]. Atrial arrhythmias are the most commonly reported types, with atrial fibrillation consultations commonly requested during the peak of the COVID-19 outbreak in New York [ 34 ]. Other less common arrhythmias included ventricular arrhythmias, ventricular tachycardia storm, atrioventricular block, inappropriate sinus tachycardia, and postural orthostatic tachycardia syndrome [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Others have written of bradycardia in adults with or without atrioventricular heart block as one of multiple cardiac complications in the setting of severe respiratory illness attributed to COVID-19. [4][5][6][7][8][9][10] Two papers speak specifically to associations between COVID-19 and relative bradycardia in adults, seen in states of high metabolic demand such as increased body temperature during which tachycardia would be expected. [11][12][13] One study found that one-third of adult patients with severe COVID-19 infection but overall stable vital signs developed sinus bradycardia at some point during the course of their illness.…”
Section: Discussionmentioning
confidence: 99%
“…They were able to manage 55% of patients remotely and were able to provide guideline and evidence-based recommendations. [ 13 ] Similar reports from other specialties like OB/GYN in which they were able to provide tele-health to 1352 patients for prenatal care, of which 61.5% were maternal fetal medicine (MFM) visits. [ 14 ] Another pilot study was reported by Renner et al from Helsinki University Hospital in Finland.…”
Section: Digital Health In Ep During Covidmentioning
confidence: 63%